2023
DOI: 10.3389/fpubh.2023.1223429
|View full text |Cite
|
Sign up to set email alerts
|

A network analysis of the long-term quality of life and mental distress of COVID-19 survivors 1 year after hospital discharge

Abstract: ObjectivesCOVID-19 survivors suffer from persistent mental distress and impaired quality of life (QOL) after recovery from the infection. However, the symptom-symptom interaction between these psychological variables remained unexplored. The present study aimed to determine the symptom network of mental distress (depression, anxiety, sleep disturbance, fatigue, and post-traumatic stress disorder) and their association with QOL among 535 COVID-19 survivors 1 year after hospital discharge.Methods9-item Patient H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Previous studies have confirmed their satisfactory psychometric properties in Chinese populations [ 39 42 ]. Following previous studies [ 43 , 44 ], a cutoff point of 10 for PHQ-9, 10 for GAD-7, and 6 for PSQI was used to determine the presence of depression, anxiety, and sleep disturbances.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have confirmed their satisfactory psychometric properties in Chinese populations [ 39 42 ]. Following previous studies [ 43 , 44 ], a cutoff point of 10 for PHQ-9, 10 for GAD-7, and 6 for PSQI was used to determine the presence of depression, anxiety, and sleep disturbances.…”
Section: Methodsmentioning
confidence: 99%
“…The current study used network modelling to explore a wide range of long COVID symptoms, departing from previous studies that focused on specific symptoms (e.g., neurobehavioral (4), mental distress (17)). The online format allowed for more convenience and accessibility, providing a broader perspective beyond high-income countries (37).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Finally, visualizing the interconnection of different symptoms can be informative for offering new perspectives on pathogenic mechanisms (16). Some previous studies have employed network analysis to explore long COVID (4,17). However, their focus was limited to neurocognitive, behavioral, and psychosocial aspects pertaining to long COVID.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there were no statistically significant differences in such network results between participants with or without any history of mental disorders and those who had or hadn’t been hospitalized. Peng P. et al (2023) found in their study on Chinese COVID-19 survivors that the most prominent symptoms included uncontrollable and excessive worry, psychomotor symptoms, intrusion, and daytime dysfunction. Additionally, daytime dysfunction and fatigue were identified as bridge symptoms in the mental disorder network and exhibited a strong association with quality of life.…”
Section: Introductionmentioning
confidence: 99%